PENGARUH KETERSEDIAAN FASILITAS TEMPAT DUDUK DI AREA SELASAR (CURB) TERHADAP KENYAMANAN PENGGUNA JASA PENERBANGAN DI BANDAR UDARA INTERNASIONAL HANG NADIM BATAM - Sudiah Putri, Nada Ghaniyyah; Martanti, Ika Fathin Resti (Jurnal Ground Handling, 2024)
The management of Hang Nadim Batam International Airport must be able to provide facilities that are appropriate for the comfort of flight service users. This is because Batam's Hang Nadim International Airport will experience an increase in the number of passenger traffic movements by 15% from 2022. This research aims to determine the effect of the availability of seating facilities in the curb area on the comfort of aviation service users at Hang Nadim International Airport Batam. This research uses a quantitative approach, a data collection method by distributing questionnaires to respondents. The sample in this study was 100 respondents with criteria >17 years and over who had used the facilities in the corridor area (curb) with data analysis using the SPSS 25 system. The results of this research show that the availability of seating facilities in the lobby area has a significant positive effect on the comfort of flight service users at Batam's Hang Nadim International Airport. This is shown by the results of data acquisition with a value of tcount > ttable, namely 10.355 > 1.984.